Highly responsive flexible strain sensor using polystyrene nanoparticle doped reduced graphene oxide for human health monitoring. (December 2018) - Gong, Tianxun; Zhang, Hua; Huang, Wen; Mao, Linna; Ke, Yizhen; Gao, Min; Yu, Bin
Abstract: A highly responsive, flexible piezoresistive strain sensor was demonstrated using laser thermal reduced graphene oxide doped with polystyrene nanoparticles. The nanoparticles alter the morphology of the sensing film by separating stacked graphene fragments and creating partially connected conducting channels, which significantly increase the resistance change under strain. Two types of distinctive resistance-changing mechanisms were observed associated with doping of nanoparticles with different sizes. Compared with graphene oxide based strain sensors, the measured gauge factor of the sensor doped with 90 nm nanoparticles can reach up to 250 under small deformation (linear region below 1.05%). Furthermore, the flexible strain sensor was applied for real-time monitoring of human body activities including swallowing process, lower back posture and pulse on neck. The demonstrated results present the potential of a viable sensing material for a number of human health monitoring applications in preventing injuries and detecting certain disease-related disorders. Graphical abstract: Image 1